Sistema de Gestión Hospitalaria para la atención de la pareja infértil. Centro Territorial de Holguín, 2021. - Rodríguez Pérez, Osvaldo George; Pérez Pupo, Annarelis; Borjas Batista, Eliecer Osvaldo; Verdecia Reyes, Julio Yamel (Revista Cubana de Informática Médica)
Introduction: Biological infertility is a disease of the reproductive system that alters the psychological and social balance of couples. In Cuba there is a program for the treatment of infertile women and the Ministry of Public Health includes in its guidelines to implement the organizational bases, work system, indicators, functions and control that guarantee the improvement of the Program, including databases where couples treated for this reason are registered. Objective: To implement a Hospital Management System for the infertile couple care in the Holguín Territorial Center. Methods: A study of technological development was carried out using postgre SQL relational database system, Odoo tool, and Python programming language. Results: SCAPI allows to manage the information of patients and their medical records; it is made up of modules that are related to each other: the general configuration module which allows you to create user profiles and permissions to interact with the system; the SCAPI module which shows and manages all the information related to the digital medical history, appointment schedules, and diagnostic means (ovarian reserve studies, spermograms, ovarian ultrasound, hormonal studies, low and high technology techniques, among others). Conclusions: Hospital Management System for the care of infertile couples allows managing fast, timely and reliable information on patients and their medical records during care consultations for infertile couples with the aim of achieving a higher quality of patient care.